2013
DOI: 10.1080/02673037.2013.758241
|View full text |Cite
|
Sign up to set email alerts
|

Elderly Mobility and the Occupancy Status of Single-Family Homes

Abstract: This research explores the occupancy status and tenure transitions of single-family homes from which elderly homeowners recently moved. First, we compare the housing and neighborhood characteristics of homes vacated by nonelderly and elderly homeowners. Then, we use a multinomial logit model to test the extent to which these characteristics are associated with the home's subsequent vacancy and tenure status. The results indicate that a lack of recent updates and modern amenities may hinder subsequent owner occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Positive aspects of home ownership are the security and stability associated with it (Dupuis and Thorns, 1998;Saunders, 1990), the possibilities to adapt the home to one's preferences (Rohe et al, 2013) and the wealth stored in the home which is available for release when needed (Aurand and Reynolds, 2013). Most previous work has shown that owners have higher SWB than renters (Zumbro, 2014;Rohe and Bassolo, 1997;Rossi and Weber, 1996;however renters had higher SWB in: Oswald et al, 2003).…”
Section: Housing Tenurementioning
confidence: 99%
“…Positive aspects of home ownership are the security and stability associated with it (Dupuis and Thorns, 1998;Saunders, 1990), the possibilities to adapt the home to one's preferences (Rohe et al, 2013) and the wealth stored in the home which is available for release when needed (Aurand and Reynolds, 2013). Most previous work has shown that owners have higher SWB than renters (Zumbro, 2014;Rohe and Bassolo, 1997;Rossi and Weber, 1996;however renters had higher SWB in: Oswald et al, 2003).…”
Section: Housing Tenurementioning
confidence: 99%
“…Focusing on in-movement rather than out-mobility, one study found that the higher-income households who are more likely to move into lower income neighborhoods are those who place less emphasis on amenities (Ellen, Horn, and O'Regan 2013). However, there is less evidence regarding housing unit transitions between owner and renter status; research on elderly households found that recent updates in the unit increased the chances of owner occupancy by the new residents (Aurand and Reynolds 2013).…”
Section: Social Distance In Housing Unit Turnovermentioning
confidence: 99%
“…Concordance on race and ethnicity is also expected to be high, and given economic inequality between groups, it will be an additional contributor to the stickiness of poverty. Elderly occupants, possibly due to a lack of updating in their units (Aurand and Reynolds 2013), are also expected to have an increased chance of being replaced by lower income in-movers. Housing units that are owner occupied are expected to have a lower chance of transitioning to poor occupants, possibly due to the greater investments in upkeep (Galster 1987).…”
Section: Introductionmentioning
confidence: 99%